218k views
0 votes
PLEASE HELP!!!!

Choose the equation below that is equivalent to 4(x - 7) - 2(x + 1) = -10

2x - 26 = -10

2 ( x - 6) = -10

4x - 28 - 2x - 2 = -10

4x - 28 - 2x +2 = -10

1 Answer

7 votes

Explanation:

=4(x)+4(-7)-2(x)-2(1) = -10

= 4x-28-2x-2= -10

therefore the third equation is equivalent to the given equation..all you need is to simplify.

Hope this Helps!!!

User Rajenpandit
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.